PENDEKATAN ARSITEKTUR RAMAH LINGKUNGAN SEBAGAI PRINSIP BANGUNAN SEKOLAH BERBASIS ALAM: Studi Kasus Green School, Bali - Anugrah, Paras; Rahayu, Elis Sri; Sanitha, Onie Dian; F. Adji, Fredyantoni; Siswadi, Rony S. (JURNAL PERSPEKTIF ARSITEKTUR, 2023)
Nature-based schools are an educational alternative that utilizes nature as the main medium for learning that is active and direct. The natural approach as the main medium of learning is expected to be able to help students understand the importance of knowing the conditions and potential of the natural environment as part of human life which is never separated from dependence on nature. Green School Bali applies the concept of learning with nature through the introduction of natural potential with the support of the scope of the building which also has a natural theme. Natural materials are designed as the main material for children's school buildings that still pay attention to the health of users, the majority of whom are elementary school students aged 6-12 years. This research will describe the material and design of the Green School Bali school building with the theme of nature and environmental friendliness using the case study method with archive collection and observation techniques so that a main material in the form of bamboo is found which is the hallmark of the school with many accompanying findings and considerations.